Spatiotemporal Variation of Hydrogen and Oxygen Stable Isotopes in the Yarlung Tsangpo River Basin, Southern Tibetan Plateau - Yan, Ya-Ni; Zhang, Jun-Wen; Zhang, Wei; Zhang, Gui-Shan; Guo, Jian-Yang; Zhang, Dong; Wu, Jie; Zhao, Zhi-Qi (Frontiers in Earth Science, 2021)
Characterization of spatiotemporal variation of the stable isotopes δ18O and δD in surface water is essential to trace the water cycle, indicate moisture sources and reconstruct paleoaltimetry. In this study, river water, rainwater and groundwater samples were collected in the Yarlung Tsangpo River (YTR) Basin before (BM) and after the monsoon precipitation (AM) to investigate theδ18O and δD spatiotemporal variation of natural water. Most of river waters are distributed along GMWL and the line of d-excess=10‰, indicating that they are mainly originated from precipitation. Temporally, the δ18O and δD of river water are higher in BM series (SWL: δD=10.26δ18O+43.01, R2=0.98) than AM series (SWL: δD=9.10δ18O+26.73, R2=0.82). Spatially, the isotopic compositions of tributaries increase gradually from west to east (BM: δ18O=0.65Lon(°)-73.89, R2=0.79; AM: δ18O=0.45Lon(°)-57.81, R2=0.70) and from high altitude to low (BM: δ18O=-0.0025Alt(m)-73.89, R2=0.66; AM: δ18O=-0.0018Alt(m)-10.57, R2=0.58), which conforms to the “continent effect” and “altitude effect” of precipitation. In the lower reaches of the mainstream, rainwater is the main source, so the variations of δ18O and δD are normally elevated in the flow direction. Anomalously, in the middle reaches, the δ18Omainstream and δDmainstream values firstly increase and then decrease. From Saga to Lhaze section, the higher positive values of δ18Omainstream are mainly caused by groundwater afflux, which has high δ18O and low d-excess values. The δ18Omainstream decreased from Lhaze to Qushui section is attributed to the combined action of the import of depleted 18O and D groundwater and tributaries. Therefore, because of the recharge of groundwater with markedly different δ18O and δD values, the mainstream no longer simply inherits the isotopic composition from precipitation. These results suggest that in the YTR Basin, if the δ18O value of surface water is used to trace moisture sources or reconstruct the paleoaltimetry, it is necessary to rule out the influence from groundwater.